Dynamics of 137Cs concentrations in agricultural products after the Chernobyl accident: cereals, potato, and vegetables - S. V. Fesenko; P. V. Prudnikov; E. S. Emlyutina; I. E. Epifanova; O. A. Shubina (Радиационная гигиена, 2023)
The purpose of the study was to analyze the regularities of 137Cs concentrations in grain, potatoes and vegetables in the areas affected the Chernobyl accident. The data describing the countermeasures in the south-western districts of the Bryansk region are given. The system of radiological monitoring of plant products is described and the relevant data are presented. Dynamics of concentrations both in grain and in potatoes and vegetables had a pronounced heterogeneous character. Reduction of 137Cs concentration in crop production (grain, potato, and vegetables) was determined by the dynamics of agrochemical countermeasures in the contaminated areas, sorption of 137Cs in soil and radioactive decay. It has been revealed that effective halflives of 137Cs in the above products during intensive implementation of rehabilitation measures (1987-1990) varied within the range from 0,7 up to 1,3 years. Subsequently, in 1991-2011, the decrease of contamination of products slowed down, and in some areas with intensive application of protective measures a certain increase of 137Cs content in products was noted. Effective half-lives during that period ranged 10.5-29 years depending on the peculiarities of application of countermeasures and soil characteristics. The pattern of the 137Cs concentrations in the grain produced in different districts from 2011 to 2021 also differed depending on the history of the countermeasures’ application in those districts in the previous periods. The estimation of the effective half-life, equal to 18.2 years, for predicting the reduction of plant product contamination in the long term after the Chernobyl accident has been suggested.